A Systems-Inspired Taxonomy of SoTL Research: Increasing the Accessibility and Visibility of this Heterogeneous Field - Miller-Young, Janice; Paul, Jeffrey W.; Rodrigues, Renato B.; Seniuk Cicek, Jillian (Teaching and Learning Inquiry, 2025)
The scholarship of teaching and learning (SoTL) is a vast, multi-epistemic field which can be challenging for new and experienced scholars to navigate. This paper introduces a systems-inspired taxonomy of SoTL designed to enhance accessibility, visibility, and knowledge organization within the field. Drawing from an iterative and extensive process involving a literature review, thematic coding of published SoTL inquiries from eight different journals, and international community consultations, the resulting taxonomy in its current form has six trees or “dimensions.” These include who is being studied, what aspects of learning are investigated, how learning is supported, where and when studies take place, why students learn, and the inquiry approaches used. The taxonomy serves multiple purposes: providing researchers with a structured way to situate their work, guiding literature and scoping reviews, and improving the discoverability of SoTL studies through more deliberate keyword selection. By adopting a systems-thinking perspective, this taxonomy balances structure with flexibility, offering a navigational tool rather than a rigid classification scheme. It is intended to be descriptive, rather than prescriptive, and should be regularly updated through ongoing community input and engagement in order to ensure it remains reflective of emerging research and practice in the field.